STRATEGI KOMUNIKASI PEMASARAN SEKOLAH DALAM PENERIMAAN PESERTA DIDIK BARU - Zulni, Abdul Hamid; Yuliawati, Elly; Hereyah, Yoyoh (MediaKom : Jurnal Ilmiah Komunikasi, 2023)
Communication concerning social life is marketing communication. An educational institution requires marketing communications due to introducing the educational institution to the wider community. This study aims to determine the school's marketing communication strategy in accepting new students at the State Islamic Senior High School (MAN) 3 Palembang, South Sumatra Province. It is known that at MAN 3 Palembang the number of new students tends to fluctuate because MAN 3 Palembang has not implemented the right marketing communication strategy. SWOT analysis theory explains the strengths, weaknesses, opportunities and threats that occur. Furthermore, in marketing science there is also STP (Segmenting, Targeting, and Positioning) as a marketing strategy. This study uses a descriptive qualitative method with a constructivism paradigm. Based on the results of the study, it shows that the school marketing communication strategy in accepting new students at the State Islamic Senior High School (MAN) 3 Palembang, South Sumatra Province, which has been carried out/so far has been running in the PPDB process, is to use a push strategy and a pull strategy. The marketing communication strategy model that can be implemented in the future by MAN 3 Palembang is to continue implementing the superior programs that have been running so far.